Sensitivity and specificity of antigen-capture ELISAs for diagnosis of Trypanosoma congolense and Trypanosoma vivax infections in cattle - Eisler, M.C.; Lessard, P.; Moloo, D.; Masake, R.A.; Peregrine, A.S. (OAU/STRC, 1999)
The FAO/IAEA Trypanosomiasis Direct Antigen-ELISA kit has been distributed to scientists holding research contracts under an IAEA Co-ordinated Research Programme in 14 sub-Saharan African countries. It is intended for improved diagnosis of bovine tsetse-transmitted trypanosomiasis as an aid to epidemiological studies and to national trypanosomiasis control programmes. The method was developed at the International Livestock Research Institute's Nairobi laboratories by Nantulya and Lindqvist (1989), and subsequently modified by scientists at the Animal Production and Health Unit at the IAEA Agriculture Laboratory, Seibersdorf, Austria (Wright et al., 1993). The most significant of these modifications are: the use of blocking agent (0.5 percent normal mouse serum) in the sample diluent buffer; use of the percentage positivity data expression system; and incorporation of internal quality assurance target values. In spite of these modifications, the basic assay configuration remains the same as that of Nantulya and Lindqvist (1989). The anti-trypanosomal monoclonal antibodies are from the original hybridoma cell lines (derived at ILRI), and are used as in the original assay configuration. In the work described here, the sensitivity and specificity of the FAO/IAEA Trypanosomiasis Direct antigen-ELISA kit was assessed in relation to trypanosome infections in cattle. ELISA responses were measured in serum of previously naive cattle following primary experimental infection with cloned populations of Trypanosoma congolense and T. vivax originating from geographically distinct locations in East and West Africa.